Effects of Biofilm Nano-Composite Drugs OMVs-MSN-5-FU on Cervical Lymph Node Metastases From Oral Squamous Cell Carcinoma - Huang, Jian; Wu, Zhiyuan; Xu, Junwu (Frontiers in Oncology, 2022)
This work was developed to the effects of biofilm composite nano-drug delivery system (OMVs-MSN-5-FU) on lymph node metastasis from oral squamous cell carcinoma. Mesoporous silica nanoparticles loaded with 5-FU (MSN-5-FU) were prepared first. Subsequently, the outer membrane vesicles (OMV) of Escherichia coli were collected to wrap MSN-5-FU, and then OMVs-MSN-5-FU was prepared. It was then immersed in artificial gastric juice and artificial intestinal juice to explore the drug release rate. Next, the effects of different concentrations of the nano-drug delivery systems on the proliferation activity of oral squamous carcinoma cell line KOSC-2 cl3-43 were analyzed. Tumor-bearing nude mice models were prepared by injecting human tongue squamous cell carcinoma cells Tca8113 into BALB/c-nu nude mice. They were injected with the OMVs-MSN-5-FU nano drug carrier system, and peri-carcinoma tissue and cervical lymph node tissue were harvested to observe morphological changes by Hematoxylin – eosin (HE) staining. The scanning electron microscope (SEM) results showed that all MSN, MSN-5-FU, OMV, and OMV-MSN-5-FU were spherical and uniformly distributed, with particle sizes of about 60nm, 80nm, 90nm, and 140nm, respectively. Among them, OMV had a directional core-shell structure. The cumulative drug release rates of artificial gastric juice in 48 hours were 61.2±2.3% and 26.5±3.1%, respectively. The 48 hours cumulative drug release rates of artificial intestinal juice were 70.5±6.3% and 32.1±3.8%, respectively. The cumulative release of MSN-5-FU was always higher than OMV-MSN-5-FU. The cumulative release of MSN-5-FU was always higher than OMV-MSN-5-FU. After injection of OMVS-MSN-5-FU, the number of cancer cells was significantly reduced and cervical lymph node metastasis was significantly controlled. HE staining results showed that OMVS-MSN-5-FU injection reduced the number of stained cells. Dense lymphocytes were clearly observed in the cortex of neck lymphocytes. The OMVs-MSN-5-FU drug delivery system can slow down the drug release rate, significantly inhibit the proliferation activity of oral squamous cancer cells, and control the metastasis of cancer cells to cervical lymph nodes.